A Comprehensive Analysis of Machine Learning Models for Real Time Anomaly Detection in Internet of Things - Sanjith, SL; George Dharma Prakash Raj, E (International Journal of Computer Sciences and Engineering, 2025)
Anomaly detection is a major requirement of the current Internet of Things (IoT) and inter-networked communication environment. This work analyzes recent and prominent contributions in the domain of Anomaly detection. The analysis is performed especially in domains related to real time operations and IoT environment. The review is performed and results from most prominent models in literature are considered for analysis. This paper discusses the working mechanisms and the major issues in Anomaly detection such as data imbalance and noise especially in IoT domain and the methods used to handle these issues. Experiments were performed using the NSL-KDD benchmark data set. Precision, False Positive Rate and Accuracy are used to analyze the effectiveness of the models.